Photocatalytic Oxidation of Formaldehyde in ZnO or SiO2 Suspensions - Hou, Guangshun; Li, Yingjie; Pang, Xucheng; Shao, Dadong (Asian Journal of Chemistry, 2012)
Photocatalytic oxidation of formaldehyde in K2SO4 solution using ZnO or SiO2 as catalyst under ambient condition is studied. The effects of UV illumination time, catalyst (ZnO or SiO2) content (m/V), HCHO initial concentration, pH and K2SO4 concentration on the photocatalytic oxidation of HCHO are determined. The presence of SiO2 (1.0 g/L) can increase the photocatalytic oxidation of HCHO (2.0 × 10-2 g/L) from 7.1 to 19.2 % after illumination time of 24 h. The photocatalytic oxidation of HCHO is dependent on pH value, but independent of ionic strength. The results are important for the application of sand (SiO2) in the treatment of HCHO pollution in eutrophic environment and for the evaluation of the removal of organic pollutants by photocatalytic oxidation in the natural environment.